Chapter Graça Morais et José de Guimarães, des humanistes du 20 ème siècle: l'art de penser le monde par le voyage - Souto, Egidia (Studi e saggi, 2021)
Starting with the theme of travel and forced migration in the contemporary world, this work aims to reflect on the different forms of travel representations and state of the world in a resilience time. Specifically, we will analyse Metamorfoses da Humanidade (2018) of Graça Morais and Nómadas e Migrantes (2018) of José de Guimarães, to understand how these artists describe the humanity and the crisis of the migrants from the artifice of the image.